The Analysis of Judge Considerations in Decision Number 0077/Pdt.P/2019/PA.Tnk Concerning Marriage Dispensation and Its Implications Viewed from Mashlahah Perspective - Yoki Pradkta, Hervin; Al-Farizi, Rifki Ilyas; Muhammad, Hasanuddin; Saefudin, Wahyu (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Marriage dispensation is the granting of marriage permits to brides who are not yet of the age specified in the law with clear reasons, for example in this study dispensation is given to brides who have been permitted to marry by their parents, what is interesting from this research is the basic considerations of judges in giving perspective marriage dispensation problem. The main problem to be examined is the judge's consideration in the decision Number 0077/Pdt.P/2019/PA.Tnk regarding the dispensation of marriage and its implications. This research is a qualitative research with literature study(library research), characteristic descriptive analytic. The results of this study are: First, the judge's consideration is the most important aspect in determining a decision that contains legal certainty, justice, and contains benefits for the parties concerned and justice seekers. Viewed from perspective problem then the granting of a marriage dispensation in the decision is in accordance with maslahah ad-daruriyyah or fit for purpose advice' in order to safeguard the five aspects of Islamic law, namely safeguarding religion, soul, intellect, lineage and property which will certainly benefit the bride and her family, if this is not continued it will result in mafsadah. Second, Implications of the Judge's Decision Number 0077/Pdt.P/2019-/PA.Tnk regarding marriage dispensation has positive implications for the bride and her family, by granting permission to marry it will clarify the status of the child, avoid negative views from society and avoid acts adultery which is prohibited by religion